2012
DOI: 10.1038/cdd.2012.42
|View full text |Cite
|
Sign up to set email alerts
|

(G2019S) LRRK2 activates MKK4-JNK pathway and causes degeneration of SN dopaminergic neurons in a transgenic mouse model of PD

Abstract: (G2019S) mutation of leucine-rich repeat kinase 2 (LRRK2) is the most common genetic cause of both familial and sporadic Parkinson's disease (PD) cases. Twelve-to sixteen-month-old (G2019S) LRRK2 transgenic mice prepared by us displayed progressive degeneration of substantia nigra pars compacta (SNpc) dopaminergic neurons and parkinsonism phenotypes of motor dysfunction. LRRK2 is a member of mixed lineage kinase subfamily of mitogen-activated protein kinase kinase kinases (MAPKKKs). We hypothesized that (G2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
153
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(162 citation statements)
references
References 41 publications
(96 reference statements)
8
153
0
1
Order By: Relevance
“…LRRK2 was able to bind to and phosphorylate MAP2K, ‐3, ‐4, ‐6 and potentially ‐7 in vitro 70, 71. Furthermore, a G2019S ‐LRRK2 transgenic mouse model showed degeneration of dopaminergic neurons in the substantia nigra concomitant with hyperphosphorylation of MAP2K4 72. Activation of MAP2K3 and MAP2K6 is stimulated by stress, cytokines and growth factors, leading to the activation of the downstream effector p38.…”
Section: Signalling Pathways Through Lrrk2mentioning
confidence: 98%
“…LRRK2 was able to bind to and phosphorylate MAP2K, ‐3, ‐4, ‐6 and potentially ‐7 in vitro 70, 71. Furthermore, a G2019S ‐LRRK2 transgenic mouse model showed degeneration of dopaminergic neurons in the substantia nigra concomitant with hyperphosphorylation of MAP2K4 72. Activation of MAP2K3 and MAP2K6 is stimulated by stress, cytokines and growth factors, leading to the activation of the downstream effector p38.…”
Section: Signalling Pathways Through Lrrk2mentioning
confidence: 98%
“…Two transgenic mouse models overexpressing human G2019S LRRK2 exhibit modest age-dependent DA neuron loss associated with accumulation of autophagosomes and mitochondrial alterations [124,125], but other G2019S LRRK2 transgenic mouse models had diminished dopamine transmission and motor deficits without detectable neuron loss [53,54]. The only I2020T LRRK2 transgenic mouse model reported to date exhibits no obvious loss of DA neurons [126].…”
Section: Direct Toxic Effects Of Lrrk2 Expression In Neuronsmentioning
confidence: 99%
“…Indeed, consistent and permanent microglial activation and subsequent production of pro-inflammatory cytokines have been shown in primary microglial cells. [52][53][54][55][56][57][58] In particular, TLR4 may be crucial in activating microglial cells and may be involved in phagocytosis. 54 Another recently published study showed that oligomeric aSyn may interact and activate TLR2 in microglial cells.…”
Section: Microglia and Astrocytes In Ad And Pdmentioning
confidence: 99%